Electron transfer-mediated enhancement of microbial reductive dechlorination of tetrachloroethylene and its impacts on key soil biogeochemical elements - Jiang, Xinrui; He, Shengzhuang; Guo, Airan; Yu, Haijuan; Xu, Yan; Li, Qingyu; Xiu, Zongming (Frontiers in Soil Science, 2025)
Electron shuttles play a critical role in mediating reductive dechlorination of tetrachloroethylene (PCE), significantly influencing the biogeochemical cycling of key elements in terrestrial ecosystems (e.g., soil). Despite their significance, the stimulatory effects of electron shuttles on the dechlorination of PCE in situ remediation remained underexplored. This study investigated the efficacy of PCE dechlorination and associated redox cycling of biogenic elements (Fe, S, and N) in three distinct habitats from Qingdao—river sediment (RS), farmland soil (FS), and chloroform-contaminated soil (CS)—using anthraquinone-2,6-disulfonate (AQDS) as an electron shuttle. The results indicated that: AQDS enhanced soil reductive capacity, lowering redox potential below −150 mV to create optimal conditions for dechlorinating microbial communities. The PCE removal efficiency was significantly improved with AQDS, increasing from 87.87% to 95.04% in RS (21 days), from 79.61% to 94.78% in FS (28 days), and from 81.48% to 89.40% in CS (35 days). Heterogeneous biogeochemical responses to PCE stress were observed across habitats. During PCE dechlorination, Fe(III) reduction was enhanced in FS and CS, but suppressed in RS, while NO3− reduction was inhibited in RS and FS but unaffected in CS. SO42− reduction accompanied PCE dechlorination across all habitats with AQDS significantly stimulating SO42− reduction. CH4 production was delayed in FS and CS (0–14 days), whereas RS exhibited the fastest production rates —1172.19 mmol/L-day. AQDS supplementation significantly increased CH4 production rates in RS (from 149.77 to 364.02 mmol/L-day during days 14-28) and CS (from 61.22 to 64.41 mmol/L-day during days 28-35), alongside elevated CO2 production, while FS displayed divergent trends. The regulatory effects of AQDS and PCE on microbial communities across different habitats further demonstrate their associated biogeochemical redox processes and PCE reductive dechlorination status. Microbial community analysis revealed that AQDS and PCE reshaped the microbiome, enriching for key functional genera such as Pelotomaculum_B, Clostridium_AF, and Desulfitobacterium, whose specific roles were habitat-dependent. These findings demonstrate that while electron shuttles can accelerate the bioremediation of chlorinated solvents, their performance and collateral effects on elemental cycling are dictated by the indigenous biogeochemical and microbial characteristics of the target environments. This underscores the critical need for habitat-specific assessments prior to the field application of electron shuttle-amended remediation strategies.